On Some New Notions and Functions in Neutrosophic Topological Spaces - I. Arokiarani (Neutrosophic Sets and Systems, 2017)
In this paper, we define the notion of neutrosophic semiopen (resp. preopen and α-open) functions and investigate relation among them. We give a characterization of neutrosophic α-open set, and provide conditions for a neutrosophic set to be a neutrosophic α-open set. We discuss characterizations of neutrosophic pre-continuous (resp. α-continuous) functions. We give a condition for a function of neutrosophic topological spaces to be a neutrosophic α-continuous function.